Modeling And Prediction of Mechanical Strength in Electron Beam Welded Dissimilar Metal Joints of Stainless Steel 304 and Copper Using Grey Relation Analysis - Ajith Raj, R; Dev Anand, M (International Journal of Engineering and Technology, 2018)
Aircraft industries witness an extensive variety of utilizations in unique welded joints thinking about the benefit of quality and high corrosion protection. In any case, joining of dissimilar materials is more mind boggling because of the distinction in material properties. In this investigation dissimilar metal joints of pure Copper plates and Stainless Steel 304 plates of 3mm thickness were welded with Electron Beam Welding. The welding input parameters like Welding speed, Beam current and Work distance liable to quality of weld are considered. Plan of analysis has been made utilizing Taguchi strategy with three levels of input values. Ultimate tensile strength and hardness number were found to decide the mechanical quality. Both the yield esteems are consolidated for expectation and optimized using Gray Relation Analysis (GRA). The impacts of the input parameters towards weld quality were analyzed using ANOVA.Â